Stages of the Failure Mode Effect and Analysis (FMEA) Method in RME Risk Analysis: Tahapan Metode Failure Mode Effect and Analysis (FMEA) dalam Analisis Risiko RME - Kristijono, Anton; Prabowo, Primus Radixto; Aggun, Tiara; Fatoni, M. Irfan (Universitas Muhammadiyah Sidoarjo, 2025)
Healthcare facilities are required to implement EMR in accordance with Minister of Health Regulation No. 24 of 2022. ICT has developed rapidly in various sectors, including the development of EMR in the health sector. Before implementing EMR, an assessment of their readiness is necessary. Analysis of health facility readiness in the EMR implementation plan is a way to identify risks that cause failure in EMR implementation. The purpose of this study was to analyze EMR risk management using Health Care Failure Mode Effect and Analysis (FMEA). This type of research is a mixed research study, with data collection through observation, in-depth interviews with triangulation, and questionnaires. The research informants were determined using the RACI Chart model. Data processing and analysis used the Miles and Hubberman model. Risk priority was determined using the USG model (urgency, seriousness, growth). The results of the study identified five risk factors: patient identification at the registration section, storage of new and existing patient surgical report files, patient registration via mobile JKN, integration with the Ministry of Health's One Healthy System, backup servers, and disk mirroring. Risk assessments varied from low to high risk. The conclusion in this study is that the implementation of EMR is inseparable from the risk of failure. The steps of the Health Care FMEA method identify and eliminate potential failures, so that appropriate risk controls can be applied to existing potential risks.